Comparison of cytology and human papillomavirus-based primary testing in cervical screening programs in the Nordic countries. (December 2021) - Partanen, Veli-Matti; Dillner, Joakim; Tropé, Ameli; Ágústsson, Ágúst Ingi; Pankakoski, Maiju; Heinävaara, Sirpa; Sarkeala, Tytti; Wang, Jiangrong; Skare, Gry Baadstrand; Anttila, Ahti; Lönnberg, Stefan
Objective: To compare primary test positivity in cytology and human papillomavirus-based screening between different Nordic cervical cancer screening programs using harmonized register data. Methods: This study utilized individual-level data available in national databases in Finland, Iceland, Norway, and Sweden. Cervical test data from each country were converted to standard format and aggregated by calculating the number of test episodes for every test result for each calendar year and one-year age group and test method. Test positivity was estimated as the proportion of positive test results of all primary test episodes with a valid test result for "any positive" and "clearly positive" results. Results: The age-adjusted rate ratio for any positive test results in primary human papillomavirus-based screening compared to cytology was 1.66 (95% CI 1.64–1.68). The age-adjusted rate ratio for clearly positive test results was 1.02 (95% CI 1.00–1.05). A decreasing rate ratio by age was seen in both any positive and clearly positive test results. Test positivity increased over time in Iceland, Norway, and Sweden but slightly decreased in Finland. Conclusions: The probability of any positive test result was higher in human papillomavirus testing than in primary cytology, even though the cross-sectional detection of a clearly positive test result was the same. Human papillomavirus testing can still lead to an improved longitudinal sensitivity through a larger number of follow-up tests and the opportunity to identify women with a persistent human papillomavirus infection. Further research on histologically verified precancerous lesions is needed in primary as well as repeat testing.